RESULTS OF THE RESEARCH OF THE ST. PANTELEIMON CHURCH NEAR HALYCH - MOHYTYCH, Ivan (Halych. Scientific work collection, 2017)
The article is devoted to the previous and new research of the St. Panteleimon church in the suburbs of ancient Halych. A unique landmark of Romanesque architecture has undergone numerous changes, rebuildings and reconstructions, so that its authenticity isn’t preserved enough. The architectural composition, style and details of the decoration of the temple testify that the masters who built it have rather Hungarian than Polish origin.